Evaluation of the Accuracy of Intraoral Digital Impression Systems and CAD and CAM Workflows for Fabricating Dental Prostheses - Ojas Anand Gajbhiye; M. Pradeep Reddy; Md. Imran; Nikhita Narayanan; Praveen Gangadharappa; Harisha Dewan (Journal of Pharmacy and Bioallied Sciences)
Background: Dental prosthesis manufacturing has undergone a radical change with the introduction of intraoral digital impression technologies and computer-aided design and computer-aided manufacturing (CAD and CAM) processes. Investigations into these systems’ accuracy in creating dental restorations that adhere to clinical standards are still underway. Materials and Methods: For this investigation, a total of 60 patients in need of single-unit crowns were chosen. They were divided into three groups of 20: Group A used intraoral digital impression systems, Group B used conventional impression procedures, and Group C combined digital impressions with CAD and CAM processes. The marginal fit and internal fit of the crowns were compared to assess the correctness of the dental prosthesis. A stereomicroscope was used to evaluate the marginal fit, and micro-CT imaging was employed to analyze the interior fit. ANOVA and Tukey’s post hoc test were used to examine the data, with a significance threshold of P < 0.05. Results: The mean marginal fit was 120 ± 15 μm for Group A, 80 ± 10 μm for Group B, and 75 ± 8 μm for Group C, according to the data. The internal fit values were 150 ± 20 μm for Group A, 90 ± 12 μm for Group B, and 85 ± 10 μm for Group C. According to statistical analysis, Group B and Group C outperformed Group A in terms of accuracy in both internal and marginal fits (P < 0.01). There was no discernible difference between Group B and Group C. Conclusion: When constructing dental prostheses, intraoral digital impression technologies and CAD and CAM workflows show better accuracy over conventional impression techniques. The greatest clinical results are obtained when digital impressions and CAD and CAM workflows are combined, indicating that these technologies need to be accepted as routine procedures in prosthetic dentistry.